Simulation of Turbulent Flows Using a Finite-Volume Based Lattice Boltzmann Flow Solver (Communications in Computational Physics, 2018)
In this study, the Lattice Boltzmann Method (LBM) is implemented througha finite-volume approach to perform 2-D, incompressible, and turbulent fluid flowanalyses on structured grids. Even though the approach followed in this study necessitatesmore computational effort compared to the standard LBM (the so calledstream and collide scheme), using the finite-volume method, the known limitations ofthe stream and collide scheme on lattice to be uniform and Courant-Friedrichs-Lewy(CFL) number to be one are removed. Moreover, the curved boundaries in the computationaldomain are handled more accurately with less effort. These improvementspave the way for the possibility of solving fluid flow problems with the LBM usingcoarser grids that are refined only where it is necessary and the boundary layers mightbe resolved better.